TINJAUAN FILOSOFIS TENTANG EVALUASI PENDIDIKAN ISLAM - Abd. Ghani (EDUTHINK: Jurnal Pemikiran Pendidikan Islam, 2022)
The position of the evaluation of Islamic education is very important to find out the extent to which the results of Islamic education are planned. Without evaluation, Islamic education will run without purpose. In general, educational evaluation also has a very strategic position in the world of education, because the results of the evaluation can be used as input in improving educational activities. There are several procedural steps in carrying out an evaluation, and these steps can be used as a reference in carrying out evaluations in general. The steps in question include: Planning, Data Collection, Data Verification and Data Analysis. The educational evaluation has a very strategic position in the world of education, because the results of the evaluation can be used as input in improving educational activities. And if it is associated with Islamic education, it is clear that Islamic teachings also pay great attention to this evaluation. As in the word of Allah SWT in the holy book of the Qur'an, it has told us that evaluation activities for human students are an important task in terms of the educational process that has been carried out by educators.